Dietary High Zinc Oxide Modulates the Microbiome of Ileum and Colon in Weaned Piglets - Yu, Ting; Zhu, Cui; Chen, Shicheng; Gao, Lei; Lv, Hang; Feng, Ruowei; Zhu, Qingfeng; Xu, Jinsong; Chen, Zhuang; Jiang, Zongyong (Frontiers in Microbiology, 2017)
Dietary zinc oxide (ZnO) at pharmacological level has been widely used to prevent and treat diarrhea in weaning piglets. Despite its importance for promoting animal health and performance, the influence of microbiome profiles in intestinal tracts by ZnO needs to be comprehensively investigated. In this study, we conducted a comparative microbial community analysis in the ileum and colon of piglets fed by either control diet, high ZnO (3,000 mg/kg) supplement or antibiotics (300 mg/kg chlortetracycline and 60 mg/kg colistin sulfate) supplement. Our results showed that both high dietary ZnO and in-feed antibiotics supplementations significantly increased 5 phyla of Spirochaetes, Tenericutes, Euryarchaeota, Verrucomicrobia, TM7 and reduced 1 phyla of Chlamydiae in ileal digesta. The relative abundance of opportunistic pathogens Campylobacterales were decreased while Enterobacteriales were increased in ZnO or antibiotics-supplemented group when compared to the control. In the colon, the phyla Euryarchaeota, the genus Methanobrevibacter, and the species Methanobrevibacter smithii were drastically increased by high dietary ZnO supplementation when compared with other groups. The microbial functional prediction analysis showed that high dietary ZnO and in-feed antibiotics had a higher abundance of transporter pathway enrichment in the ileum when compared with the control. While in the colon high dietary ZnO had a higher abundant enrichment of methane metabolism involving energy supply when compared with other groups. Both high dietary ZnO and antibiotics increased the microbiota diversity of ileal digesta while they decreased the microbiota diversity of the colonic digesta. Collectively, these results suggested that dietary ZnO and in-feed antibiotics supplementations presented similar effect on ileal microbiota, and mainly affected the non-predominant microbiota.